Tarbawi Values in QS. at-Taubah:122 as the Foundation of Islamic Educational Objectives - Intan Wardatul Karimah; Cucu Surahman; Elan Sumarna; Zakia Fitri Nabila (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2025)
This study analyzes QS. at-Taubah verse 122 through a tafsir tarbawi approach to identify its relevance to the objectives of Islamic education. Unlike previous studies that focused on partial aspects such as the obligation to seek knowledge or teacher professionalism, this research offers a comprehensive framework that interprets the verse as a conceptual foundation of Islamic education. Using a qualitative descriptive method with a library research design, the study examines classical and contemporary tafsir sources (At-Tabari, Al-Qurthubi, Ibn Katsir, Al-Maraghi, Al-Munir, Al-Azhar) and cross referencing them with modern Islamic education literature. Data were thematically analyzed to identifytarbawi values that inform the purpose and direction of Islamic education. The findings identify five main pillars of Islamic educational goals: (1) specialization of knowledge (thaifah), (2) deep understanding of religion (tafaqquh fid-din), (3) social responsibility (tandzir), (4) moral and behavioral transformation (tahdzir), and (5) intergenerational knowledge transmission. These pillars establish an integrated and transformative vision of Islamic education system that harmonizes cognitive, moral, and spiritual dimensions. The findings offer a fresh interpretive contribution to contemporary discussions on Islamic educational objectives and their alignment with concepts such as lifelong learning and character education.